Dimensions of Interest in Using E-Wallets in Online Transportation Service - I Gusti Ayu Purnamawati; Gede Adi Yuniarta; Elly Herliyani (Master of Management, School of Business and Management, Petra Christian University, 2023)
There are still many MSME actors who have not used e-wallets, especially in using online transportation. This paper examines the Utilitarianism, trust, risk perception, reputation, and costs of e-wallet users' interest in online transportation. This research uses quantitative methods. A questionnaire was used to collect data from 110 small and medium-scale entrepreneurs in Bali Province. Multiple linear regression analysis tests are used to test the interest of e-wallet users. The results show that the utilitarian variables, trust, and reputation, positively and significantly affect e-wallet user interest. At the same time, risk perceptions and cost do not affect e-wallet user interest. These costs are burdensome for consumers to purchase mobile devices to take advantage of digital payment services, so it takes time and effort to consider adopting new technology. Inclusive finance is an important entry point for inclusive growth; e-wallets also help Micro, Small, and Medium Enterprises currently being promoted by the government to support the economy. TAM is a model that theoretically helps predict and explain user acceptance of information technology. Digital payment solutions allow consumers and merchants to use social media to buy and sell goods and services to create new economic opportunities.